Implementasi Pemberian Hand Massage Terhadap Penurunan Tingkat Kecemasan Pre Operasi Pada Pasien Sectio Caesarea Dengan Anastesi Spinal di RSU Muhammadiyah Siti Aminah Bumiayu - Febriyanti, Vivin Dwi; Sukmaningtyas, Wilis; Adriyani, Fauziyah Hanum Nur (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Sectio caesarea is a surgical delivery process where the baby is removed through an incision in the mother's stomach (laparotomy) and uterus (hysterectomy). Each delivery method has a psychological impact on the mother, especially anxiety. One strategy for dealing with anxiety using non-pharmacological techniques is providing reflexology or hand massage. The aim of this PkM is to provide hand massage to reduce tension and reduce anxiety in preoperative caesarean section patients with spinal anesthesia. The method used was to provide hand massage twice in 10 minutes to 30 participants and use the APAIS measuring instrument in the VK Room. The results of this activity showed that the level of anxiety before implementation in the anxious category was 15 participants (50.0%), seriously anxious was 12 participants (40.0%) and mildly anxious was 3 participants (10.0%). After implementation, the majority of participants were moderately anxious, 19 (63.3%), mildly anxious, 9 (30.0%), and severely anxious, 2 (6.7%). The decrease in participants' anxiety had an average value before the hand massage was 59% and after the hand massage was 45% with a difference of 14%.